The Impact of Clinical Pharmacist Tele-follow-up on Diabetic Patient’s Readmission Due to Reinfection of Methicillin-Resistant Staphylococcus Aureus (MRSA) in Iraqi Patients - faris, kawthar; Besmah M.Ali Ibrahim, Besmah M.Ali Ibrahim; Osama Zuhair Salman, Osama Zuhair Salman; Zainab Jumaa Qasim, Zainab Jumaa Qasim; oudah, Ameer; Ayad Okab, Aaya; K.Aldiwan, Jawad (Iraqi Journal of Pharmaceutical Sciences, 2024)
Abstract There are many risk factors significantly associated with readmission of diabetic patients after discharge like surgical site reinfection with methicillin-resistant Staphylococcus aureus which has been demonstrated to be associated with more amputations, longer hospitalization , increase healthcare costs and increased mortality .This study was to describe the impact of clinical pharmacist tele-follow-up on diabetic patient’s readmission due to reinfection of methicillin-resistant Staphylococcus aureus, rate of referral to inpatients team and, return visits to the emergency department, 203 patients who were randomized into two groups. Group A (interventional group) 103 patients and group B (control group) 100patients who are discharge from hospital after diabetic foot amputation. The primary endpoint was the reduction in the readmission due to reinfection by methicillin-resistant Staphylococcus aureus, reduce the referral to in patients team and fewer return to the emergency department. there was significant differences between the two groups in rates of readmission, referral to their inpatients team, and return visits to the emergency department with (P-value =0.004, 0.00017 ,and0.002 ) respectively. Conclusion the pharmacist tele-follow-up was associated with decrease in rates of readmission, fewer referrals to in patients team and decrease in return visits to the emergency department. Keywords: pharmacist tele follow-up , diabetic patients , MRSA